Advances in Injectable and Self‐healing Polysaccharide Hydrogel Based on the Schiff Base Reaction - Mo, Chunxiang; Xiang, Li; Chen, Yuping (Macromolecular rapid communications., 2021)
Injectable hydrogel possesses great application potential in disease treatment and tissue engineering, but damage to gel often occurs due to the squeezing pressure from injection devices and the mechanical forces from limb movement, and leads to the rapid degradation of gel matrix and the leakage of the load material. The self‐healing injectable hydrogels can overcome these drawbacks via automatically repairing gel structural defects and restoring gel function. The polysaccharide hydrogels constructed through the Schiff base reaction own advantages including simple fabrication, injectability, and self‐healing under physiological conditions, and therefore have drawn extensive attention and investigation recently. In this short review, the preparation and self‐healing properties of the polysaccharide hydrogels that is established on the Schiff base reaction are focused on and their biological applications in drug delivery and cell therapy are discussed. This review summarizes the recent advances in the injectable and self‐healing polysaccharide hydrogel based on the Schiff base reaction. It introduces the mechanism of their self‐repairing, their fabrication and their biomedical application in the delivery of drug and cell. The focus is on the modification strategies and methods of the polysaccharides applied in gel preparation.